2000
DOI: 10.1521/pedi.2000.14.1.84
|View full text |Cite
|
Sign up to set email alerts
|

Standardization of the Hare Psychopathy Checklist-Revised in a Spanish Prison Sample

Abstract: This investigation examined the reliability, validity, and factor structure of the Hare Psychopathy Checklist-Revised (PCL-R) in male adult Spanish prison populations (n = 117). The interrater reliability and internal consistency coefficients were high, and similar to those obtained in other countries. This data provides support for the homogeneity and unidimensionality of the psychopathy construct in Spanish male prison samples. The analysis of factor structure also replicated the two factor solution of previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0
26

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 5 publications
4
32
0
26
Order By: Relevance
“…30, nº 1 (enero) year 2000. This research also validated the PCL-R in our country, through a study which proved that psychopathy is also a valid and reliable construct in Spanish prison samples (Moltó, Poy & Torrubia, 2000).…”
Section: The Current Situation Of the Psychopathic Intimate Partner Bsupporting
confidence: 57%
See 1 more Smart Citation
“…30, nº 1 (enero) year 2000. This research also validated the PCL-R in our country, through a study which proved that psychopathy is also a valid and reliable construct in Spanish prison samples (Moltó, Poy & Torrubia, 2000).…”
Section: The Current Situation Of the Psychopathic Intimate Partner Bsupporting
confidence: 57%
“…In 1991, the concept was only operational with samples of male prisoners. Recently, however, in the second edition of the PCL-R published in 2003, and the currently available Spanish adaptation (Moltó, Poy & Torrubia, 2000), the concept has also shown itself to be both valid and reliable in the female population, even for the normative data concerning women prisoners (Hare, 2003).…”
Section: The Psychopathic Profile: Essential Characteristicsmentioning
confidence: 99%
“…El Hare's Psychopathy Checklist-Revised (PCL-R; Hare, 1991Hare, , 2003 es el instrumento de mayor influencia en la actualidad para la detección de la psicopatía en el interior de las prisiones (salvador et al, 2015). Este se ha utilizado no solo en investigación y con fines clínicos, sino también dentro del sistema de justicia criminal para influir en la toma de decisiones en sentencias (DeMatteo et al, 2014;Lloyd, Clark y Forth, 2010), la asignación de grado en prisión, de permisos temporales o de libertad condicional (Guy, Kusaj, Packer y Douglas, 2015;Moltó, poy y torrubia, 2000), como instrumento de valoración de riesgo de violencia futura (Harris, Boccaccini y Murrie, 2015; Olver y Wong, 2015) y para la adecuación a programas de tratamiento (spaans, Barendregt, Haan, Nijman y de Beurs, 2011). Este agrupa dos factores: el primero refiere aspectos afectivos e interpersonales, mientras que el segundo recoge la información referida al estilo de vida y la conducta antisocial.…”
Section: Perfil Del Psicópata Institucionalizado Sin Comportamiento Cunclassified
“…One of such studies (Molto, Poy, & Torrubia, 2000) found Factor 2 to be significantly correlated with violent offenses such as rape (.24) and assault (.24), while In summary, the literature indicates that the predictive utility of the PCL-R for general offending and violence lies primarily on Factor 2 and perhaps facet 4 in particular. This does not mean that the same pattern holds true for sex-offending.…”
Section: Psychopathy and Violencementioning
confidence: 99%